Participatory Empowerment and Gender Equality in Dryland and Coastal Communities of Plampang, Sumbawa - Sudarli, Sudarli; Hayati, Hayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Dryland farming and coastal-island communities in eastern Indonesia have long been positioned at the periphery of national development, despite hosting substantial natural and human-capital assets. Plampang Subdistrict in Sumbawa Regency contains both typologies within a single administrative boundary, with the transmigration settlement units SP1, SP2, and SP3 representing maize-and-cattle dryland systems, and the hamlets of Labuhan Ujung and Labuhan Jontal representing small-scale fisheries economies. This narrative literature review synthesises sixty published works dated 2014-2026 to map the conceptual landscape of community empowerment, citizen participation, and gender equality, and to draw out a context-sensitive empowerment model. The review applies content, comparative, and critical analysis to peer-reviewed journal articles, foundational monographs, and government documents. Findings indicate that observed levels of participation cluster in the tokenism band of Arnstein’s ladder, while women shoulder a disproportionate share of post-harvest and processing labour without commensurate decision-making authority. A five-stage Input-Process-Output-Outcome-Impact framework is proposed, underpinned by participation, gender equality, sustainability, local wisdom, and equity as cross-cutting principles. The model offers a practical scaffold for sub-national governments, higher-education institutions, and community organisations seeking to design integrated, inclusive, and ecologically grounded interventions for similar rural-coastal landscapes across the Indonesian archipelago.